Figure skating coaching in the contemporary sport culture : Finnish figure skating coaches' perceptions about their work - Mälkki, Kati (2016)
Coaching as a profession in Finland in perceived as a challenging job. Lack of appreciation and support, scarce resources, and demanding working environment are placing coaches under a lot of pressure. In addition, coaches play a key role in the lives of their athletes and are therefore dealing with a variety of expectations and demands. These are not always set by the coaches themselves, but also from outside stakeholders, such as parents of the athletes, and national and international sport governing federations. On one hand coaches need to be demanding, authoritarian, and goal-oriented, but on the other hand, they need to be empathetic, friendly and supportive. During the past few decades, perceptions and understanding about what coaching as a profession is and requires, has been under discussion.